THIS IS NOT THE WAY WE DO TO SOLVE THE PROBLEM: THE LITERATURE COLLEGE PERCEPTIONS ON ANA KARENINA’S LIFE - Aam Alamsyah; Santosa Santosa; Radik Darmawan (Universitas Bandar Lampung, 2022)
he study analyzed the concept of feminism based on the readers’ perceptions, who are the active literature students. The study was conducted in mixed method in order to allow the researchers to employ more instruments and eliciting more varied data. There were 20 students of the literature students, who were recruited purposefully. These students were the ones, who have completed the novel in their previous semester. The findings indicated that, despite being viewed as an interesting novel, most of the participants tended to perceive that the main character’s behavior was not always morally acceptable. In fact, the action in committing adulterous relationship with her illegal partner was considered immoral. Despite supporting the action of the main character in pursuing happiness as the main objective of marriage and partially accepting divorce as one of the potential solutions, most of the participants perceived that adultery is not an acceptable way to solve the problem. The participants also considered that dialogue between the couple should be done so that they could solve their problem amicably. In sum, most of the participants agreed that feminism is important as it can provide the women with the chance to stand on a par with the other counterparts. However, they believe that feminism will never endorse such betrayal in the name of equality of women’s right.